Avaliação da função diastólica do ventrículo esquerdo em obesos graves em pré-operatório para cirurgia bariátrica - Tavares, Irlaneide da Silva (2011)
Obesity is a multifactorial chronic disease, associated with increased cardiovascular risk, that produces hemodynamic changes, in cardiac structure and function, increasing the risk of heart failure, especially the diastolic; what is important to evaluate these patients more carefully. The aim of this study is to evaluate left ventricular diastolic function in severe obese in preoperative for bariatric surgery. This is an observational, prospective and analytical study. Were evaluated in 132 patients, severely obese, asymptomatic, with normal systolic function that were in the preoperative evaluation for bariatric surgery. Stratified into three groups, according to diastolic function, the group Nl comprised 61 patients with normal diastolic function, the group DD mild, consisted of 24 patients with mild diastolic dysfunction and the group DD M/S composed of 41 patients with moderate diastolic dysfunction (pseudonormal pattern) and 06 patients with severe diastolic dysfunction (restrictive pattern). After stratification, we compared the clinical and echocardiographic characteristics among groups. Of the 132 patients, 97 (73.5%) were women. The mean age was 38.5 ± 10.5 years and average BMI was 43.7 ± 7.2 kg/m². 48 patients had obesity class II and 84 grade III obesity. The cardiovascular risk factors that showed significant differences between groups Nl vs DD mild and Nl vs DD M/G were: metabolic syndrome with 67.5% (81 patients), hypertension with 59.8% (79 patients) and diabetes mellitus with 25.2% (32 patients). Regarding clinical values we found significant differences among groups in age, waist circumference and systolic blood pressure. Regarding echocardiographic variables, we found a larger left atrial diameter, left ventricular diastolic diameter, left atrial volume at 4 and 2 chambers, index of left atrial volume, index of left ventricular mass to body surface, and this index for height, in the groups with DD mild and DD M/S vs Nl. The higher prevalence of left ventricular diastolic dysfunction in pre-clinical phase in severe obese patients justifies the need for a careful echocardiographic assessment using joint analysis of all available echocardiographic techniques, in order to identify individuals at high risk for heart failure, so that early intervention measures are adopted.